(untitled) (Studia austriaca, 2022)
Focusing on the example of the so-called “Augsburger Messer” in Thomas Bernhard’s Amras, the paper explores the possibility of overcoming the barriers to a hermeneutical reading of Bernhard’s texts through the exploitation of literary things. By comprising both its material and its symbolic dimension the micro analysis of the “Augsburger Messer” suggests coupling the eclectic potential of things in literary texts with Bernhard’s additive and associative style. Eventually, this approach not only opens up a new perspective on Amras as one of Bernhard’s most remarkable texts, but also presents his writing as one that is deeply permeated with the traumatic structures of violence and (Austrian) history.